1976
DOI: 10.1093/infdis/133.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Hypersensitivity to Fungal Antigens in Mice. I. Use of the Intradermal Skin and Footpad Swelling Tests as Assays of Active and Passive Sensitization

Abstract: Mice were sensitized to Coccidioides immitis and Candida albicans antigens and tested for sensitivity by the intradermal and footpad swelling methods. In mice actively sensitized with killed antigen, antigen-specific intradermal and footpad induration responses occurred 24 and 48 hr after sensitization. Antigen-specific intradermal and footpad responses were transferred to normal mice with spleen cells from immune animals. Such responses were also transferred with normal spleen cells that had been incubated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1977
1977
1994
1994

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Coccidioides antigen consisted of a sonically treated arthrosporeand mycelial-phase culture of thiomerasol-inactivated C. immitis. The stock antigen as prepared was termed a 1:5 dilution (5). Candida antigen consisted of sonically treated, heat-killed C. albicans serotype A (5).…”
Section: Methodsmentioning
confidence: 99%
“…Coccidioides antigen consisted of a sonically treated arthrosporeand mycelial-phase culture of thiomerasol-inactivated C. immitis. The stock antigen as prepared was termed a 1:5 dilution (5). Candida antigen consisted of sonically treated, heat-killed C. albicans serotype A (5).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, when comparative assessment of sensitization with either live blastoconidia or heat-killed cells was carried out, the largest increase in footpad thickness and highest number of mice with a positive footpad test were obtained with heat-killed 35 cells [28,29]. The DH responses (mean ± SE) which were recorded in sensitized normal mice at 24 and 48 h in this study were [16,28]. However, the biological activity of the DPE preparation in the mouse footpad test was clearly different from that of the two other antigens used: (1) the net swelling recorded after 24 and 48 h were equivalent while peak responses clearly occurred at 24 h when HKS, SCM and other subcellular extracts o f C. albicans were injected in mice [30]; (2) the local inflammatory response elicited by DPE in un primed mice was more intense than those recorded with HKS or SCM as net nonspecific swelling were 0.584±0.055 at 24 h and 0.328±0.030 at 48 h; (3) this preparation stim ulated greater DH responses in primed alloxan-diabetic mice than in primed normal controls ( fig.…”
Section: Discussionmentioning
confidence: 79%
“…and heat-killed at 60°C for I h. This cell suspension was then sonically disrupted at 4°C (100 W for 5 min, repeated three times) and used [16].…”
Section: Preparation O F Heat-killed Cell Sonicate Antigen (Hks)mentioning
confidence: 99%
“…Rifkind et al (39) reported that antigen-specific delayed hypersensitivity against C. albicans was increased in mice immunized with killed antigen. Also in our present study, delayed hypersensitivity was increased in mice immunized with live C. albicans in saline or killed C. albicans in CFA.…”
Section: Discussionmentioning
confidence: 99%